A gênese da referenciação-tópica em processos de escritura de histórias em quadrinhos da Turma Da Mônica: criação textual de alunas recém-alfabetizadas - Silva, Dennys Dikson Marcelino da (2015)
The main objective of this paper was to analyze excerpts in both dialogue transcriptions and school manuscripts produced by a couple of female pupils, who had recently undergone a literacy program, in the second year of Elementary School, in a public school from the city of Maceió, state of Alagoas, Brazil. The analyses were carried out at the moment in which the pupils were submitted to activities involving the work with comics, in classroom environment. Inserted in field of Textual Genetics (TG), we have taken for granted that each of these movements of creation (written and oral) was a version of the process of text genesis. As part of our theoretical-methodological basis, we have found support in the investigations on the writing process in act and school manuscripts, proposed by Calil (2008, 2009); relevant considerations on the comics, their narrative units as well as their metaphorical and kinetic formulations (ACEVEDO, 1990; VERGUEIRO, 2004; RAMOS, 2009; DIKSON & CALIL, 2013; LINS, 2008); the relevance of semiotics for the apprehension of plural texts, its tripartite sign division and the insertion of the comics as a multiple-semiotic locus by nature (SANTAELLA, 1983, 2002; PIERCE, 1977; ECO 1980); the notions proposed by the TG relating the variety of versions produced by the scriptor, who is always split by the lines and erasures in the manuscripts [school] (GRÉSILLON, 1994, 2007; FERRER, 2002; DE BIASE, 2010; WILLEMART, 1993; CALIL, 2008, 2014; LIMA & CALIL, 204); the investigations concerning reference and referencing in the productions and construction of textual processing (MONDADA & DUBOIS, 2003; MONDADA, 2005; CAVALCANTE, 2010, 2011; KOCH, 2003, 2005; MARCUSCHI & KOCH, 1998; CORTEZ & KOCH, 2013), as well as the way in which the supertopic, the topic, the frame and the discourse topic frames are formulated and/or kept in the engendering of textual construction (KOCH & ELIAS, 2010; KOCH, 1992, 1996, 2000; KOCH et. al., 1996; LINS, 2008). Thus, we have discussed, through the analyzes and comparisons of each version, be it written or spoken, of each one of the three activities developed by the same couple of pupils - whether the dyad was able to incorporate the characteristics which formulate the genre in study or how it starts to be absorbed by the discourse functioning of the comics; that is to say, which textual-discourse referencing, produced and projected by the two pupils, took place from the structuring semiotic of the activities, so as to have (or not) written language acquisition, and how the discourse topics were, which keep both the meaning of the stories and interaction of the characters involved in them, were being formulated. We have concluded that three movements were of primordial importance in order for this appropriation to take place: immersion in school genre, written practice in the classroom and, mainly, teaching interference. Data show that between the first written activity (including the dialogues which have generated all of them) and the second one, there was an enunciative turning, from the position taken by the pupil “in the role of image descriptor” to the position “in the role of comic writer”, and, between the two first activities and the third one, there was the stabilization of written appropriation (topic-referential). The pupils, therefore, have moved in an enunciative way, from a textual writing, which describes the comics, to a path of genesis of comic creation within the perspective desired by the teacher in the classroom.